Incidence and risk factors of acute kidney injury following transcatheter aortic valve replacement. Issue 12 (December 2016) - Thongprayoon, Charat; Cheungpasitporn, Wisit; Srivali, Narat; Kittanamongkolchai, Wonngarm; Greason, Kevin L; Kashani, Kianoush B
Abstract: Aim: This study aimed to determine the incidence and risk factors of acute kidney injury (AKI) following transcatheter aortic valve replacement (TAVR). Methods: We included all adult patients undergoing TAVR for aortic stenosis from 1 January 2008 to 30 June 2014 at a tertiary referral hospital. AKI was defined based on Kidney Disease: Improving Global Outcomes criteria. We performed a multivariate logistic regression to identify factors associated with post‐procedural AKI occurrence. Results: Three hundred eighty‐six patients met the inclusion criteria, of which 106 (28%) developed AKI. In multivariate analysis, AKI development was independently associated with a transapical approach (odds ratio (OR), 2.81; 95% confidence interval (CI), 1.72–4.65 compared with transfemoral approach) and the need for an intra‐aortic balloon pump (OR, 9.11; 95% CI, 1.77–68.29). Higher baseline renal function (OR, 0.78 per 10 mL/min per 1.73 m 2 increment in glomerular filtration rate; 95% CI, 0.68–0.87) was significantly associated with a decreased risk of AKI. After adjustment for the Society of Thoracic Surgeons' risk score, post‐procedural AKI development remained significantly associated with an increased in‐hospital (OR, 4.74; 95% CI, 1.39–18.48) and 6‐month mortality (OR, 4.66; 95% CI, 2.32–9.63). Conclusion: In a cohort of patients undergoing TAVR for aortic stenosis, AKI commonly occurred and was significantly associated with increased mortality. Baseline renal function, procedure approach and the need for circulatory support were important predictive factors for post‐procedural AKI occurrence. Summary at a Glance: Transcatheter Aortic Valve Replacement is a novel treatment for aortic stenosis in patients at high risk of complications from surgical aortic valve replacement. This paper reports the risk factors for Acute Kidney Injury following this procedure, and the associated mortality, based on a single center's experience.